How nutrition-smart agriculture can help build resilience against the “Three C” crises of climate, conflict and COVID-19 - Baral, Arun (2022)
We hear a growing chorus of warnings from members of the food and nutrition security community about the dire consequences of the war in Ukraine on global rates of hunger and malnutrition. Arif Husain, chief economist at the World Food Programme, noted recently that threats in numerous countries to food production and availability from the “Three C’s” — climate, conflict, and COVID-19 — are rapidly being compounded by the “Three F’s” — spiking food, fuel, and fertiliser prices. According to the Food and Agriculture Organisation, the number of undernourished people worldwide could increase by 8 to 13 million this year alone. Even households which may not be particularly dependent on imported or purchased foods — including hundreds of millions of smallholder farming families in Africa and Asia — are likely to feel the effects of the downward spiral of global trade on their ability to produce food. This is in large part due to higher prices for key farming inputs — particularly fertilisers — which were already on the upswing prior to the war in Ukraine and are now increasing even more quickly.